1997
DOI: 10.1016/s0029-7844(97)00294-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Interleukin-6 During Pregnancy and During Term and Preterm Labor

Abstract: Compared with antepartum gravidas, those in term or preterm labor had significantly higher concentrations of maternal serum interleukin-6 concentrations; extremely elevated levels were found in patients whose preterm labor was associated with intrauterine infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
66
1
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 17 publications
6
66
1
5
Order By: Relevance
“…221 There were five studies, all in symptomatic women who presented with threatened preterm labour, which evaluated serum IL-6 as a predictor for spontaneous preterm birth. 235,[237][238][239][240] Two studies provided information for more than one category of either population 103 or type of IL-6 specimen. 235 Appendix 5, Table 92 summarises individual study characteristics.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…221 There were five studies, all in symptomatic women who presented with threatened preterm labour, which evaluated serum IL-6 as a predictor for spontaneous preterm birth. 235,[237][238][239][240] Two studies provided information for more than one category of either population 103 or type of IL-6 specimen. 235 Appendix 5, Table 92 summarises individual study characteristics.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…This could be explained by the fact that IL-6 has both pro-and antiinflammatory properties. The classification of IL-6 as a Th1-type cytokine in studies on preterm labor 56,57 or as a Th2 type cytokine in early pregnancy [58][59][60][61] remains controversial. Recently, it has been demonstrated that IL-6 is involved in the promotion of Th2 differentiation and the inhibition of Th1 polarization.…”
Section: Commentmentioning
confidence: 99%
“…3,[157][158][159][160][161] It has also earned the role of diagnostic marker in periodontal disease. 162,163 A study of murine maternal responses to P. gingivalis during pregnancy 164 showed that P. gingivalis dissemination to the uterus has to occur for fetal growth retardation (FGR).…”
mentioning
confidence: 99%